Responsiveness of Minimal Clinically Important Change for the Persian Functional Rating Index in Patients with Chronic Low Back Pain - Noureddin Nakhostin Ansari; Shiva Komesh; Soofia Naghdi; Zahra Fakhari; Parisa Alaei (Asian Spine Journal, 2019)
Study Design A prospective, within-group cohort study of 46 patients with chronic low-back pain (CLBP). Purpose To assess the responsiveness of the Persian Functional Rating Index (PFRI) and to determine the minimal clinically important change (MCIC) of the PFRI in a cohort of patients with CLBP. Overview of Literature The FRI is an instrument for assessing pain and disability in patients with low-back pain. No study so far has examined the responsiveness of the PFRI. Methods Forty-six patients with CLBP with a mean age of 50.33±14.28 completed the PFRI, the Persian Roland–Morris Disability Questionnaire (PRMDQ), and a Visual Analog Scale (VAS) before and after 10 physiotherapy sessions. A Global Rating of Change Scale (GRCS) was completed after treatment. Results The changes in PFRI scores were statistically significant using the paired t-test (p<0.001). The PFRI revealed high effect sizes (range, 0.93–1.82). The PFRI showed significant correlations with the VAS (0.86), the PRMDQ (0.66), and the GRCS (0.45). The area under the receiver operator characteristic curve for the PFRI was good (0.76; 95% confidence interval, 0.56–0.95). The MCIC for PFRI was 10.63 points. Conclusions The results supported the responsiveness of the PFRI in patients with CLBP and showed the amount of change in PFRI scores perceived as worthwhile by the patients.